The Orthographic Ambiguity of the Arabic Graphic System: Evidence from a Case of Central Agraphia Affecting the Two Routes of Spelling - Assia Boumaraf; Sonia Bekal; Joël Macoir (Behavioural Neurology)
The Arabic writing system includes ambiguities that create difficulties in spelling. These ambiguities relate mainly to the long vowels, some phoneme-grapheme conversions, lexical particularities, and the connectivity of letters. In this article, the first to specifically explore acquired spelling impairments in an Arabic-speaking individual, we report the case of CHS, who presented with agraphia following a stroke. Initial testing indicated substantial impairment of CHS’s spelling abilities in the form of mixed agraphia. The experimental study was specifically designed to explore the influence of the orthographic ambiguity of the Arabic graphemic system on CHS’s spelling performance. The results revealed that CHS had substantial difficulties with orthographic ambiguity and tended to omit ambiguous graphemes. Some of the errors she produced suggested reliance on the sublexical route of spelling, while others rather reflected the adoption of the lexical-semantic route. These findings from a case involving a non-Western, non-Indo-European language contribute to discussions of theoretical models of spelling. They show that CHS’s pattern of impairment is consistent with the summation hypothesis, according to which the lexical-semantic and the sublexical routes interactively contribute to spelling.